2015
DOI: 10.1007/s10584-015-1342-1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the impacts of climate change on nitrogen losses and crop yield in a subsurface drained field

Abstract: The effect of climate change on crop production and nitrate-nitrogen (NO3-N) pollution from subsurface drained fields is of a great concern. Using the calibrated and validated RZWQM2 (coupled with CERESMaize and CROPGRO in DSSAT), the potential effects of climate change and elevated atmospheric CO2 concentrations (CO2) on tile drainage volume, NO3-N losses, and crop production were assessed integrally for the first time for a corn-soybean rotation cropping system near Gilmore City, Iowa. RZWQM2 simulated resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
45
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 28 publications
12
45
2
Order By: Relevance
“…Corre-Hellou et al, 2007). Process-based models such as DSSAT, APSIM, RZWQM, Hybrid-Maize, Adapt-N as well as commercial models are routinely used in this high production region to forecast crop yields (Morell et al, 2016), evaluate nitrogen rates to maize (Malone et al, 2010; Puntel et al, 2016; Sela et al, 2017), and benchmark management practices (Thorp et al, 2008;Wang et al, 2016) and climate change impacts (Wang et al, 2015;Paustian et al, 2016;Jin et al, 2017;Schauberger et al, 2017). To our knowledge, the validity of the root parameters used in the above modeling studies have not been evaluated.…”
Section: Root Front Velocitymentioning
confidence: 99%
“…Corre-Hellou et al, 2007). Process-based models such as DSSAT, APSIM, RZWQM, Hybrid-Maize, Adapt-N as well as commercial models are routinely used in this high production region to forecast crop yields (Morell et al, 2016), evaluate nitrogen rates to maize (Malone et al, 2010; Puntel et al, 2016; Sela et al, 2017), and benchmark management practices (Thorp et al, 2008;Wang et al, 2016) and climate change impacts (Wang et al, 2015;Paustian et al, 2016;Jin et al, 2017;Schauberger et al, 2017). To our knowledge, the validity of the root parameters used in the above modeling studies have not been evaluated.…”
Section: Root Front Velocitymentioning
confidence: 99%
“…By the end of the century, atmospheric CO 2 is projected to rise to approximately 650 ppm CO 2 equivalent under RCP 4.5 and 1,370 ppm CO 2 equivalent under RCP 8.5 (Moss et al 2008). Although rise in CO 2 equivalent is unaccounted for, prior studies have concluded that this will have minimal impact on the agricultural water balance (Field et al 1995;Wang et al 2015).…”
Section: Michigan Lake Eriementioning
confidence: 99%
“…For example, Ohio is projected to experience a greater increase in temperature and greater difference in the number of days with heavy precipitation than Iowa by midcentury (Pryor 2014). Singh et al (2009) and Wang et al (2015) projected that future climate would increase subsurface drainage discharge in Iowa, but differences in rainfall and temperature between Ohio and Iowa could affect subsurface drainage discharge differently in these two states. To determine how climate change will impact subsurface drainage discharge within the Western Lake Erie Basin, it is necessary to evaluate the water balance with localized climate projections.…”
mentioning
confidence: 99%
“…There has been several model studies on how soil parameters affect drain flow (Ma et al, 2007;Muma et al, 2014;Tiemeyer et al, 2007; and also studies on how the drain network set-up affect drain flow (Moriasi et al, 2013;Nangia et al, 2010;Walker et al, 2000;Wang, Mosley, et al, 2006). There has also been a number of studies on how the precipitation input and future climate change affect drain flow (Bosch et al, 2014;Tiemeyer et al, 2007;van Roosmalen, Sonnenborg, & Jensen, 2009;Wang, Qi, Xue, Bukovsky, & Helmers, 2015). However, the effect of deeper geology on drain flow has not been given much attention, and most drain models neglect the deeper geology and only cover the upper few meters.…”
mentioning
confidence: 99%